Elaboración de un programa de acondicionamiento físico a través del baile para reducir el índice de obesidad del centro educativo “Quito” de san francisco del chasqui parroquia Pastocalle de la ciudad de Latacunga en el año lectivo 2012 – 2013 - Columba Rojas, Norma del Pilar (2013)
The present research has as purpose create awareness in the teachers and parents, through them transmit to students the importance of dance in the teaching of Physical Culture and the benefits that will get when be applied through the developing a fitness Program through dance, what lead to improve the physical performance, abilities and skills, which should detach what this will serve as a tool of teaching-learning in the students of the Educative Center "Quito”. It is important to recoverthe value of the movement and rhythmin the educational context, therefore, in the process of learningasmovementand rhythm contribute to goodcognitivedevelopmentof the studenttoachievea comprehensive training andabetterlifestyle.The Development of the Fitness Program by means of the dance will serve as support to analyze the causes and consequences of obeseness in children, identifying the lack of control of parents toward physical activity, the abuse of the use of technology, which does not allow creating habits to avoid sedentary in the students of the Educational Center “Quito”.